Emissions mitigation by control of biomass feeding in an industrial biomass boiler - L. Valente; L. A. C. Tarelho; V. A. F. Costa (Energy Reports, 2020)
The objective of this work is the experimental investigation and characterization of the influence of biomass feeding on combustion efficiency of an industrial biomass boiler. The collected experimental data relate the biomass feeding control with the operating conditions and boiler performance parameters. Two different methods to control of the biomass feeding are considered. One consists on the manually controlled biomass feeding through the boiler control system. The other consists on an automatic control, with the screw-feeder controlled by the boiler control system. Boiler control system governs the introduction of the biomass material into the furnace based on the O2 content of the combustion flue gas stream. Results show that the biomass feeding into the furnace significantly affects the combustion process and the pollutant emissions (e.g., CO and NO).
Keywords: 330; Biomass; CO; content; Feeding system; Fixed grate industrial boiler; NO